Alternate Modes of Photosynthate Transport in the Alternating Generations of Physcomitrella patens - Regmi, Kamesh C.; Li, Lin; Gaxiola, Roberto A. (Frontiers in Plant Science, 2017)
Physcomitrella patens has emerged as a model moss system to investigate the evolution of various plant characters in early land plant lineages. Yet, there is merely a disparate body of ultrastructural and physiological evidence from other mosses to draw inferences about the modes of photosynthate transport in the alternating generations of Physcomitrella. We performed a series of ultrastructural, fluorescent tracing, physiological, and immunohistochemical experiments to elucidate a coherent model of photosynthate transport in this moss. Our ultrastructural observations revealed that Physcomitrella is an endohydric moss with water-conducting and putative food-conducting cells in the gametophytic stem and leaves. Movement of fluorescent tracer 5(6)-carboxyfluorescein diacetate revealed that the mode of transport in the gametophytic generation is symplasmic and is mediated by plasmodesmata, while there is a diffusion barrier composed of transfer cells that separates the photoautotrophic gametophyte from the nutritionally dependent heterotrophic sporophyte. We posited that, analogous to what is found in apoplasmically phloem loading higher plants, the primary photosynthate sucrose, is actively imported into the transfer cells by sucrose/H+ symporters (SUTs) that are, in turn, powered by P-type ATPases, and that the transfer cells harbor an ATP-conserving Sucrose Synthase (SUS) pathway. Supporting our hypothesis was the finding that a protonophore (2,4-dinitrophenol) and a SUT-specific inhibitor (diethyl pyrocarbonate) reduced the uptake of radiolabeled sucrose into the sporangia. In situ immunolocalization of P-type ATPase, Sucrose Synthase, and Proton Pyrophosphatase – all key components of the SUS pathway – showed that these proteins were prominently localized in the transfer cells, providing further evidence consistent with our argument.